THEORIES AND MODELS OF SOCIOLINGUISTICS - Abidova Umida Rustamovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Sociolinguistics explores the intricate relationship between language and society, focusing on how social structures influence language use and variation. This article provides an overview of key theories and models in sociolinguistics, including variationist theory, speech community models, accommodation theory, and critical sociolinguistics. The goal is to present a foundation for understanding how language functions within different social contexts.